Nylon composition as well as preparation method and application thereof
By using nylon, pigment red, PE and EVA compositions in nylon materials, the melt-encapsulated pigment is formed and the nylon segment movement is promoted, the fluorescence problem in nylon materials is solved, and the red with small amount of toner added and no fluorescent color is achieved Nylon compositions reduce pigment usage and cost, improve material performance and cost-effectiveness.
Patent Information
- Application Number
- CN202411314962.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
It is difficult to realize a red nylon composition with a small amount of toner addition and no fluorescence in the nylon material in the prior art, and the existing methods have an impact on the performance of the material, high cost and large waste of pigments.
The preparation method of nylon composition is adopted, including nylon, pigment red, PE and EVA, and the melt-encapsulated pigment is formed through the combination of PE and EVA, which weakens the contact between pigment and nylon, reduces the solubility of pigment, and promotes the nylon chain segment through thermal annealing. Exercise to avoid pigment-dyeing phenomenon.
A red nylon composition with small toner addition and no fluorescence is achieved, reducing the amount and cost of pigment, improving the cost-effectiveness of the material, and broadening the application range of other colorants in polar plastics.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material coloring, and in particular relates to a nylon composition and a preparation method and application thereof. Background Art
[0002] Nylon is also called polyamide, and its English name is Nylon or Polyamide (PA for short). Nylon has the characteristics of high strength, wear resistance, light weight, good insulation, high temperature resistance, and chemical corrosion resistance. These characteristics make nylon widely used in many fields. In the industrial field, nylon is used to manufacture mechanical parts such as bearings, gears, and pipes due to its high strength and wear resistance. In the electronic and electrical industry, nylon is used for wire and cable insulation layers, electrical switches and other components due to its good insulation and high temperature resistance. In the construction industry, nylon is often used to make architectural decorations and sealing materials due to its weather resistance and easy processing. In the aerospace field, nylon is used to manufacture lightweight and high-strength components due to its lightweight and high-strength characteristics.
[0003] Nylon processing usually adds color powder for dyeing to meet the diverse needs of the market and consumers. Through dyeing, nylon products can obtain rich colors and patterns, thus enhancing their beauty and appeal.
[0004] However, many pigments will produce hydrogen bond interactions with the amide bonds of nylon during processing and cause pigment-dye phenomenon, changing the color of the pigment, accompanied by the appearance of strong fluorescence [J. Colloid Interface Sci, 1999, 216 (1): 189], resulting in a significant decrease in the weather resistance and color stability of plastic products. Therefore, the choice of pigments in colored nylon is greatly limited. At present, the commonly used red pigments in the color matching of nylon compositions are DPP pigments and perylene pigments. Although these two types of pigments have a great advantage in terms of molecular structure stability, they still cannot completely avoid the pigment-dye phenomenon. According to public information, dissolved DPP dye single molecules can promote molecular aggregation through stimulation methods such as mechanical force and thermal annealing to achieve color change and fluorescence quenching. However, in the field of plastic coloring, due to the influence of the movement of polymer chain segments, it is difficult for pigment / dye molecules in this environment to achieve structural transformation. DPP molecules dissolved in nylon need to be heat treated at a high temperature of 180°C for 5h to achieve molecular aggregation and restore the original red color. This method has a great influence on the mechanical properties of nylon itself.
[0005] A Chinese patent application with publication number CN 109735102 A discloses a non-fluorescent red nylon material and a preparation method thereof. The application suppresses the fluorescence of red nylon by significantly increasing the amount of DPP pigment. The amount of DPP needs to be increased to more than 1.5wt%. This content of DPP will damage the material properties and also lead to waste of pigment and increased cost.
[0006] The prior art lacks a red nylon composition that has a small amount of color powder added, is non-fluorescent, and can quickly achieve reverse conversion from pigment to dye. Summary of the invention
[0007] The object of the present invention is to solve the above technical problems and provide a red nylon composition with less toner added and no fluorescence.
[0008] Another object of the present invention is to provide a method for preparing the above nylon composition.
[0009] Another object of the present invention is to provide applications of the nylon composition.
[0010] The present invention is achieved through the following technical solutions: A nylon composition, characterized in that it contains the following components in parts by weight: Nylon 93-99 parts; Pigment red 0.02-0.05 parts; PE 0.5-5 parts; EVA 0.5-10 parts; The sum of the weight proportions of PE and EVA is greater than or equal to 2 parts.
[0011] Preferably, the sum of the weight parts of PE and EVA is 2-5 parts.
[0012] Preferably, the PE is selected from any one or more of HDPE and LDPE; preferably HDPE.
[0013] Preferably, the weight ratio of PE:EVA is 1:(0.1-10); more preferably 1:(1-7), and even more preferably 1:(2-4).
[0014] Preferably, the weight average molecular weight of the PE is preferably 50,000-250,000, and more preferably 60,000-200,000.
[0015] Preferably, the melting point of the PE is preferably 90°C-150°C, and more preferably 100°C-135°C.
[0016] Preferably, the weight percentage of VA in the EVA is preferably 15%-45%.
[0017] Preferably, the nylon is selected from any one or more of nylon 6, nylon 66, nylon 56, nylon 612, nylon 510, and nylon 12, more preferably nylon 6 and nylon 66, and even more preferably nylon 6.
[0018] The relative viscosity of the nylon is preferably 2.30-37.00, the melting point is preferably 170-270°C, and the density is preferably 0.60-1.20 g / cm 3 .
[0019] Preferably, the pigment is selected from bis(p-chlorophenyl)-1,4-diketopyrrolopyrrole, 2,9-dimethyl-5,12-dihydroquinolin[2,3-B]acridine-7,14-dione, 2,9-dichloro-5,12-dihydroquinolin[2,3-B]acridine-7,14-dione, 1-(4-chloro-o-sulfonic acid-5-tolylazo)-2-naphthol barium salt, 3-hydroxy-4-[(4-methyl-2-sulfonic acid phenyl)azo]-2-naphthoic acid calcium salt, N,N'-1,4-phenylene-bis[4-(2,5-dichlorophenyl)azo]-3-hydroxynaphthalene-2-carboxylic acid Any one or more of amine, 2,9-bis[4-(phenylazo)phenyl]anthracene[2,1,9-def:6,5,10-d'e'f']diisoquinoline-1,3,8,10(2H,9H)-tetraone, preferably any one or more of bis(p-chlorophenyl)-1,4-diketopyrrolopyrrole, 2,9-bis[4-(phenylazo)phenyl]anthracene[2,1,9-def:6,5,10-d'e'f']diisoquinoline-1,3,8,10(2H,9H)-tetraone, and more preferably bis(p-chlorophenyl)-1,4-diketopyrrolopyrrole.
[0020] When the amount of pigment red is too small, the fluorescence will be enhanced and it will be more difficult to restore the color; although excessive use can suppress fluorescence to a certain extent and help color control, it will lead to a significant increase in costs and cause appearance defects such as color powder spots on the surface of the colored plastic, and the impact of fluorescence on weather resistance cannot be ignored.
[0021] Those skilled in the art can add 0.1-2 parts by weight of auxiliary agent according to actual needs; the auxiliary agent is selected from any one or more of antioxidants, lubricants and light stabilizers.
[0022] Preferably, the antioxidant is selected from any one or more of hindered phenol antioxidants and aromatic amine antioxidants, and the lubricant is selected from any one or more of esters or sodium tannic acid salts.
[0023] The present invention also provides a method for preparing the above nylon composition, comprising the following steps: S1: Dry the nylon thoroughly; S2: mixing the components uniformly and extruding the nylon composition through a screw extruder; S3: Packing the nylon composition into bags.
[0024] Preferably, the drying temperature in S1 is 110-120° C., and the drying time is 2-4 hours.
[0025] The present invention also provides application of the nylon composition for preparing electric tool parts.
[0026] The invention has the following beneficial effects: PE and EVA form a melt to encapsulate the pigment, thereby reducing the contact between the pigment and nylon, and avoiding the pigment-dye phenomenon caused by the hydrogen bond interaction between the pigment particles and the amide bonds of the nylon; the low polarity of PE and EVA helps to reduce the solubility of the pigment in nylon; the lubricity of PE and EVA helps to increase the mobility of the nylon chain segments and reduce the heterogeneous nucleation of the pigment molecules and nylon; and EVA helps to adjust its compatibility in the nylon composition and prevent precipitation failure.
[0027] In addition to increasing the mobility of nylon chain segments through lubricity, PE and EVA can also promote the movement of nylon chain segments by affecting the temperature of thermal annealing. PE and PA have poor compatibility. If only PE is added, it will be detrimental to the mechanical properties of the nylon composition. If only EVA is added, the melting point of the system will be lower than 100°C. Although it can promote movement, this temperature does not reach the optimal movement state of the nylon chain segment itself.
[0028] Through the combined effect of PE powder and EVA, the fluorescence problem of pigments in nylon is solved and color restoration is achieved; the technical solution of the present application can greatly reduce the amount of pigments used and save color matching costs. By compounding PE and EVA, better effects can be achieved while reducing costs, significantly improving cost-effectiveness, and broadening the application scope of other colorants in polar plastics. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0030] The raw materials used in the present invention come from: Nylon 6: purchased from Jiangsu Haiyang Technology Co., Ltd., brand HY-2500A, relative viscosity 2.45±0.04, melting point 215-220℃, density 1.135-1.145g / cm 3.
[0031] Nylon 66: purchased from INVISTA Nylon Chemical (China) Co., Ltd., brand PA66 U3200, relative viscosity 30.0-35.0, melting point 263°C, density 0.65-0.70 g / cm 3 .
[0032] Nylon 56: purchased from Shanghai Cathay Biotechnology Co., Ltd., brand E-6631, relative viscosity 2.37±0.05, melting point 265±3℃, density 1.17 g / cm 3 .
[0033] Nylon 612: purchased from DuPont, brand name Zytel-158, melting point 218°C, density 1.06 g / cm 3 Nylon 12: purchased from Shandong Dongchen Ruisen New Material Technology Co., Ltd., brand PA1212, melting point 178-185℃, density 1.01-1.03 g / cm 3 .
[0034] PE1: HDPE, purchased from Dow Chemical, brand ELITE™ AT 6900, weight average molecular weight 200,000, melting point 134°C.
[0035] PE2: LDPE, purchased from Sinopec Chemical Sales (Guangdong) Co., Ltd., brand LDPE MG70, weight average molecular weight 60,000, melting point 102°C.
[0036] EVA1: purchased from Taiwan Plastics Industry Co., Ltd., brand EVA 7350M, VA content 18%.
[0037] EVA2: purchased from Sinochem Quanzhou Petrochemical Co., Ltd., brand EVA UL00628, VA content 28%.
[0038] PP: purchased from CNOOC Shell Petrochemical Co., Ltd., brand PP EP548R, melting point 164-170℃, density 0.9g / cm 3 .
[0039] Pigment 1: Bis(p-chlorophenyl)-1,4-diketopyrrolopyrrole, purchased from BASF under the brand name Irgazin® Red K 3840 SQ (Pigment Red 254).
[0040] Pigment 2: 2,9-dimethyl-5,12-dihydroquinolin[2,3-B]acridine-7,14-dione, purchased from Zhejiang Yongquan Chemical Co., Ltd., brand 122B (R203) (Pigment Red 122).
[0041] Pigment 3: 2,9-dichloro-5,12-dihydroquinolin[2,3-B]acridine-7,14-dione, purchased from Titanium Sun Chemical, brand R252 (Pigment Red 202).
[0042] Pigment 4: 3-hydroxy-4-[(4-methyl-2-sulfonylphenyl)azo]-2-naphthoic acid calcium salt, purchased from Shenzhen Dingtai Chemical Co., Ltd., brand L4B (R216) (Pigment Red 57:1).
[0043] Pigment 5: N,N'-1,4-phenylene-bis[4-(2,5-dichlorophenyl)azo]-3-hydroxynaphthalene-2-carboxamide, purchased from BASF, brand K3540 (Pigment Red 166).
[0044] Pigment 6: 2,9-bis[4-(phenylazo)phenyl]anthracene[2,1,9-def:6,5,10-d'e'f']diisoquinoline-1,3,8,10(2H,9H)-tetraone, purchased from BASF, brand K3911 (Pigment Red 178).
[0045] Pigment 7: 1-(4-chloro-o-sulfonic acid-5-methylphenylazo)-2-naphthol barium salt, purchased from Shenzhen Tianlaibao Pigment Co., Ltd., brand Graphtol Red LC-CN09 (Pigment Red 53:1).
[0046] Antioxidant 1: purchased from Tianjin Li'anlong New Materials Co., Ltd., hindered phenol antioxidant, brand RIANOX1098.
[0047] Antioxidant 2: purchased from CBITEC, spirophosphite antioxidant, brand name REVONOX® 608.
[0048] Lubricant 1: available from Emery Oleochemicals, brand LOXIOL G 32.
[0049] Lubricant 2: available from Clariant, brand Licomont NAV101 PWD.
[0050] Light stabilizer: purchased from Cytec Surface Technology (Shanghai) Co., Ltd., brand name CYASORB® UV-3808PP5.
[0051] The preparation method of the nylon composition of the embodiment and the comparative example is as follows: the nylon is fully dried at a drying temperature of 120° C. for a drying time of 2 hours; the components are uniformly mixed according to a proportion, and plastic particles are extruded through a screw extruder; and the plastic particles are packaged into bags.
[0052] Various test methods: (1) Fluorescence intensity: The plastic particles were injection molded into color plates for testing. The fluorescence intensity was measured using a Horiba Jobin Yvon LabRAMHR800 fluorescence spectrometer, where the slit was set to 1 nm, the excitation wavelength was 400 nm, and the color plate was placed at 45°.
[0053] (2) Hue: Plastic particles are injected into color plates for testing, and the hue is measured using an X-rite Color-Eye 7000A spectrophotometer. Hue h represents color information, that is, the position of the spectral color. This parameter is expressed as an angle, with a value range of 0~360°: if calculated counterclockwise from red, red is 0°, green is 120°, and blue is 240°. Their complementary colors are: yellow is 60°, cyan is 180°, and purple is 300°. The smaller the value, the redder the color.
[0054] (3) Two-month outdoor simulated weathering test color difference: Place the color plates evenly in the aging box and use 0.80 W / (m 2 The artificial aging test was carried out for 2 months using a xenon lamp with an irradiation intensity of 0.177 nm. Samples were collected every seven days for color testing. The color difference (∆E) was characterized by a spectrophotometer (X-rite Color-Eye 7000A).
[0055] Table 1: Weight parts of each component of nylon composition and test results of Examples 1-10
[0056] It can be seen from Examples 4-9 that when nylon 6 is used as nylon, the prepared nylon composition has better performance in the three test results of fluorescence intensity, hue, and color difference of simulated weathering test.
[0057] It can be seen from Examples 4 and 10 that when HDPE is selected as PE, the prepared nylon composition has better performance in various performance tests.
[0058] Table 2: Weight parts of each component of nylon composition of Examples 11-20 and test results
[0059] It can be seen from Examples 4 and 11-14 that the present application can achieve better results by adding a small amount of PE and EVA.
[0060] It can be seen from Examples 4 and 15-20 that the present application is versatile in terms of pigment selection, and the selection of specific pigments has little impact on the technical effect of achieving no fluorescence in the present application.
[0061] Table 3: Weight parts of each component of nylon composition of comparative examples 1-4 and test results
[0062] In Comparative Example 1, only PE is added without EVA, and the sum of the weight portions of PE and EVA is less than 2 portions. The fluorescence intensity is greater than 0.4, the hue is greater than 35, and the color difference of the simulated weathering test is greater than 20.
[0063] It can be seen from Comparative Example 2 that by replacing EVA with PP, the test results of the nylon composition are within an acceptable error range, and PP has no effect on achieving the technical effect of the present application.
[0064] Comparative Example 3 is a blank control group without adding PE and EVA.
[0065] The pigment addition amount in Comparative Example 4 is 0.01. Compared with Example 4, the three test results are all significantly different from those in Example 4. It can be seen that the lower limit of the pigment addition amount has a significant impact on the results of fluorescence intensity, hue and color difference of simulated weathering test. It is speculated that the reason is that the pigment red aggregates and turns red. When the addition amount of the pigment red is low, the pigment red is basically dissolved in the resin. Therefore, the smaller the addition amount, the stronger the fluorescence, and the more difficult it is to restore the color.
Claims
1. A nylon composition, characterized in that: By weight, it contains the following ingredients: Nylon 93-99 parts; Pigment red 0.02-0.05 parts; PE 0.5-5 parts; EVA 0.5-10 parts; The sum of the weight proportions of PE and EVA is greater than or equal to 2 parts.
2. A nylon composition according to claim 1, characterized in that: The PE is selected from any one or more of HDPE and LDPE, preferably HDPE.
3. A nylon composition according to claim 1, characterized in that: The weight ratio of PE:EVA is 1:(0.1-10); preferably 1:(1-7), and more preferably 1:(2-4).
4. A nylon composition according to claim 1, characterized in that: The nylon is selected from any one or more of nylon 6, nylon 66, nylon 56, nylon 612, nylon 510, and nylon 12, preferably nylon 6 or nylon 66, and more preferably nylon 6.
5. A nylon composition according to claim 1, characterized in that: The pigment is selected from bis(p-chlorophenyl)-1,4-diketopyrrolopyrrole, 2,9-dimethyl-5,12-dihydroquinolin[2,3-B]acridine-7,14-dione, 2,9-dichloro-5,12-dihydroquinolin[2,3-B]acridine-7,14-dione, 1-(4-chloro-o-sulfonic acid-5-tolylazo)-2-naphthol barium salt, 3-hydroxy-4-[(4-methyl-2-sulfonic acid phenyl)azo]-2-naphthoic acid calcium salt, N,N'-1,4-phenylene-bis[4-(2,5-dichlorophenyl)azo]-3-hydroxynaphthalene-2-carboxamide, Any one or more of 2,9-bis[4-(phenylazo)phenyl]anthracene[2,1,9-def:6,5,10-d'e'f']diisoquinoline-1,3,8,10(2H,9H)-tetraone, preferably any one or more of bis(p-chlorophenyl)-1,4-diketopyrrolopyrrole and 2,9-bis[4-(phenylazo)phenyl]anthracene[2,1,9-def:6,5,10-d'e'f']diisoquinoline-1,3,8,10(2H,9H)-tetraone, and more preferably bis(p-chlorophenyl)-1,4-diketopyrrolopyrrole.
6. A nylon composition according to claim 1, characterized in that: By weight, the invention further comprises 0.1-2 parts of auxiliary agents; the auxiliary agents are selected from any one or more of antioxidants, lubricants and light stabilizers.
7. A nylon composition according to claim 6, characterized in that: The antioxidant is selected from any one or more of hindered phenol antioxidants and aromatic amine antioxidants, and the lubricant is selected from any one or more of esters or sodium tannic acid salts.
8. A method for preparing a nylon composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Dry the nylon thoroughly; S2: mixing the components uniformly and extruding the nylon composition through a screw extruder; S3: Packing the nylon composition into bags.
9. The preparation method according to claim 8, characterized in that: The drying temperature in S1 is 110-120°C and the drying time is 2-4 hours.
10. Use of a nylon composition according to any one of claims 1 to 7 for preparing electric tool parts.
Citation Information
Patent Citations
Nylon composite material as well as preparation method and application thereof
CN118109040A
New tetrazo-dyestuffs
GB860278A
Dyeable compositions comprising polypropylene,polyamide and ethylene copolymer
US3454512A
Cited By
Nylon composition, preparation method therefor and use thereof
WO2026061269A1